Micorrização em gramíneas de pastagem natural sob pastoreio rotativo - Taschetto, Fernanda Maurer (2017)
Sourthern Brazil natural grasslands present great diversity of vegetal species, being very important for the cattle rearing and conservation of the natural resources. This diversity is related to the diversity of soil microorganisms. Among these, some soil fungi of the Filo Glomerycota form mycorrhizal associations, increasing the absorption of phosphorus beyond the depletion zone. Also, the species present differences between mycorrhizal colonization, due to the characteristic of each species or due to soil modifications. The hypothesis of this work is that the response to the mycorrhizal colonization of native grass species of the Pampa biome is differentiated. That species with low mycorrhizal colonization, are species of slower growth, with conservation of resources and species with the highest mycorrhizal colonization, present a more accelerated growth, with fast recycling of nutrients. The objective of this work was to evaluate the mycorrhizal association of native arbuscular fungi with the roots of four native grass species belonging to two groups of contrasting growth rate of natural pastures of Rio Grande do Sul, under different intervals between defoliation. The work was carried out in a natural pasture area of the Federal University of Santa Maria. Mycorrhizal colonization of four native grass species (Andropogon lateralis, Axonopus affinis, Aristida laevis and Paspalum notatum) was studied in two 375 and 750 degree day (GD) rest intervals. There was no interaction between the period of root sampling and the species studied. In the interval of 375 GD, the species P. notatum and A. affinis presented better mycorrhizal colonization, the latter did not differ from the other two species. There was no difference between species for the 750 GD interval. In general, there was good mycorrhization for the species, evidencing the importance of this association for the development and persistence of these species in an acid and nutrient poor soil, such as occurs in a large part of these natural grasslands.